2019
DOI: 10.1186/s13046-019-1314-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal transfer of p-STAT3 promotes acquired 5-FU resistance in colorectal cancer cells

Abstract: Background Acquired resistance remains a limitation of the clinical use of 5-fluorouracil (5-FU). Because exosomes, are important vesicles participating in intercellular communication, their contribution to the development of acquired 5-FU resistance needs to be elucidated. In this study, we aimed to examine the underlying mechanisms of exosomes from 5-FU resistant cells (RKO/R) in sustaining acquired 5-FU resistance in sensitive cells (RKO/P). Methods Exosomes from a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 41 publications
2
70
0
Order By: Relevance
“…Studies have shown that up to 25% of CRC patients have distant metastasis at diagnosis and that the median overall survival (OS) of patients with mCRC is 28 months [28]. Although surgery combined with chemoradiotherapy can prolong the lifespan and alleviate the pain associated with the disease, mCRC patient prognosis remains poor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that up to 25% of CRC patients have distant metastasis at diagnosis and that the median overall survival (OS) of patients with mCRC is 28 months [28]. Although surgery combined with chemoradiotherapy can prolong the lifespan and alleviate the pain associated with the disease, mCRC patient prognosis remains poor.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our results indicated that GW4064 could act cooperatively with oxaliplatin to inhibit STAT3 and subsequently regulate downstream targets to induce tumor cell apoptosis and pyroptosis. Excessive STAT3 activation in CRC is an important signaling mechanism that mediates tumor progression and drug resistance to chemotherapies (43). Blocking STAT3 signaling has been demonstrated to restore drug sensitivity in CRC (39).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, it has recently been shown that phosphorylated STAT3 is present in exosomes from 5-fluorouracil (5-FU) resistant colorectal cancer cells, which contributes to acquired 5-FU resistance [ 149 ]. Given the importance and efficiency of exosomes in intercellular and interorgan communication [ 150 , 151 ], these findings not only add another complexity to STAT3 regulation, but also pave a new way to inhibit the oncogenic function of STAT3, as well as to delivery STAT3 inhibitors via exosomes.…”
Section: Targeting Stat3 For Cancer Immunotherapymentioning
confidence: 99%